Spent brewery grains for improvement of thermal insulation of ceramic bricks - Ferraz, Eduardo (2021)
One by-product of the brewing process is a waste containing spent grains (barley malt and maize grits). In the brewing process, this cake is composed mainly of organic matter containing high fiber content, provided by the separation of suspended particles through wort filtration. The study presented here was carried out to assess if the spent brewery grains could be recycled through their incorporation in a paste used in the manufacture of ceramic bricks, and how such incorporation affects some of the physical properties, namely mechanical strength, porosity, and thermal conductivity of the ceramic material. The main objective of the study was to decrease the thermal conductivity of the ceramic paste without significant losses of the mechanical strength of the final product. Spent brewery grains (SBG) characterized by powder X-ray diffraction, X-ray fluorescence spectrometry, scanning electron microscopy, thermogravimetry, differential scanning calorimetry, and heat of combustion were used as an additive (pore-forming agent) to a brick paste, characterized by powder X-ray diffraction, particle-size analysis, mechanical strength, plasticity index, and thermal conductivity determinations. Powder mixtures obtained by addition of 5, 10, and 15% by weight of dry SBG to brick raw material (SBG-to-brick paste weight) were assembled. The powder mixtures were extruded and the green probes were dried (105°C) before slow firing at 900, 950, and 1,000°C. Drying and firing shrinkages and mechanical bending strengths were investigated in addition to bulk density, open porosity, water absorption, and thermal conductivity of the fired samples. The mixture of ceramic paste with SBG fired up to 900°C with an incorporation of SBG of 5% by weight was found to reach a compromise between the highest mechanical bending strength (15 MPa) and the lowest thermal conductivity (0.46 Wm−1K−1). When compared with the ceramic paste without SBG incorporation, a diminution of 12 and 28% of the values of these properties, respectively, was obtained.